Relationships of Nurses' Perceptions of Antimicrobial Stewardship, Interprofessional Collaborative Competence, Speaking Up Climate for Patient Safety, and Participation in Antimicrobial Stewardship - Ji Hye Lee; Eun Jung Kim (Journal of Fundamental Nursing Science, 2026)
Purpose: This study aimed to examine the relationships among registered nurses' perception of antimicrobial stewardship (AMS), interprofessional collaborative competence, speaking-up climate for patient safety, and their participation in AMS programs. Methods: A cross-sectional survey was conducted with 144 nurses working in general wards and intensive care units at a general hospital in Seoul. Participants completed self-administered questionnaires, and the data were analyzed using the independent t-test, one-way analysis of variance, Pearson correlation coefficients, Spearman rank correlation analysis, and multiple regression analysis. Results: The mean scores were as follows: AMS participation, 3.12 out of 5; perception of AMS, 5.14 out of 10; interprofessional collaborative competence, 3.57 out of 5; and speaking-up climate, 3.85 out of 5. AMS participation was positively correlated with perception of AMS (r=.26, p=.002), interprofessional collaborative competence (r=.33, p